ACTIVATION OF EDUCATIONAL AND COGNITIVE ACTIVITY OF YOUNGER SCHOOLCHILDREN BY MEANS OF DIDACTIVE GAMES ON THE EXAMPLE OF THE SUBJECT "ENGLISH LANGUAGE " - Zebo Botirova, Ph.D; Gulmira Rasulova,; Nasirdinova Sevara, (Research Focus International Scientific Journal, 2023)
This study investigates the use of didactic games as a pedagogical tool to activate the educational and cognitive activity of younger schoolchildren, focusing on the subject of "English Language." The purpose of the study was to explore the effectiveness of integrating games into the curriculum for enhancing language learning in primary education. To achieve this, a structured methodology was employed, involving the selection of a sample of schoolchildren, the creation and implementation of didactic games, and the analysis of their impact on the participants. The results demonstrated that didactic games effectively engage students and enhance their language acquisition and cognitive skills. The findings underscore the potential of incorporating game-based learning strategies into the educational system. This study contributes to the ongoing discourse on innovative pedagogical approaches and their role in fostering children’s educational and cognitive development.